Fate of nitrogen/trace metals species during combustion and gasification of biomass - Petrolati, Andrea (Cranfield University, 2010)
This thesis focused on the fate of nitrogen and trace metals species from combustion and gasification of biomass. The effect of process parameters on the release of these species during pilot-scale combustion and gasification of biomass was investigated and the information used to identify methods for the reduction of these species. The investigation focused on Miscanthus and Dried distillers’ grains with solubles (DDGS). The pilot-scale test rigs used were a fluidised-bed combustor and a fixed-bed downdraft gasifier. The two fuels were analysed by means of proximate, ultimate and ash analysis. The process parameters monitored were temperatures, gas flow, gas composition and ash composition and the process parameters studied are bed temperature and equivalence ratio. The different nitrogen content of the two fuels plays an important role in the emission. Both bed temperature and air to fuel ratio have demonstrated to have an important influence in the release of nitrogen oxides in combustion and ammonia in gasification, therefore they can be used to mitigate the emission of these species in the flue gas. Both processes are affected by the high alkali metals content of the fuels for the tendency to form low melting composites. Differences have been highlighted in the metal distribution between combustion and gasification. The different nitrogen and ash content of the two fuels make the results of the present thesis applicable to predict the behaviour of other biomass fuels according to the fuel characteristics. The scale of the tests performed allowed highlighting which methods can be used to control the emission of nitrogen and trace metal species. Moreover, the investigation highlighted major drawbacks in the use of biomass fuels in both fluidised bed and fixed bed technology due to ash properties.
Keywords: Miscanthus; DDGS; bed temperature; equivalence ratio